1983
DOI: 10.1016/0014-5793(83)81156-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of yeast phosphorylase by phosphorylase kinase and cAMP‐dependent protein kinase

Abstract: Yeast phosphorylase is phosphorylated and activated by a cyclic AMP‐independent protein kinase (called phosphorylase kinase) and a cyclic AMP‐dependent protein kinase. Only in the presence of both kinases is phosphorylase fully activated and phosphorylated. No evidence was found for the presence of two phosphorylation sites as an identical phosphopeptide pattern of phosphorylase is obtained after phosphorylation by either one or both kinases. The kinases probably phosphorylate identical sites but recognize dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
2

Year Published

1985
1985
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 5 publications
1
29
0
2
Order By: Relevance
“…It is well known that the enzymes catalyzing the degradation of reserve carbohydrates, glycogen phosphorylase and trehalase, are activated by cyclic AMP (cAMP)-dependent phosphoryla- tion (10,(24)(25)(26). It will be interesting to investigate whether the reduction in amounts of reserve carbohydrates in rgrl cells is associated with an elevated level of intercellular cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the enzymes catalyzing the degradation of reserve carbohydrates, glycogen phosphorylase and trehalase, are activated by cyclic AMP (cAMP)-dependent phosphoryla- tion (10,(24)(25)(26). It will be interesting to investigate whether the reduction in amounts of reserve carbohydrates in rgrl cells is associated with an elevated level of intercellular cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…One trait expected for such mutants is reduced glycogen accumulation. This is because the enzymes glycogen phosphorylase and glycogen synthase are two substrates for cAMP-dependent protein kinase that are activated and inhibited, respectively, by phosphorylation (20,21,54). Conceivably, the additional traits associated with sral deletions reflect the modulation of additional cAMP-dependent protein kinase substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that levels of glycogen and trehalose in yeast cells change dramatically in response to a variety of different physiological situations (29,31,48). The enzymes involved in synthesizing and breaking down these carbohydrates are regulated through the cyclic AMP (cAMP)-dependent kinase system in yeasts (22,36,49,50,52,53). Glycogen and trehalose levels, in fact, have been useful phenotypic indicators for studying various mutants in the RAS, adenylate cyclase, and cAMP kinase genes (16,46,47).…”
mentioning
confidence: 99%